Gas barrier laminate and packaging bag

The gas barrier laminate, with an optimized basis weight ratio of paper base material to sealant film, addresses the challenges of environmental suitability and bag-making compatibility, achieving strong, transportable, and environmentally friendly packaging solutions.

JP2025069801APending Publication Date: 2025-05-01TOPPAN HOLDINGS INC

Patent Information

Application Number
JP2023179747
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-05-01

AI Technical Summary

Technical Problem

Existing gas barrier laminates, such as those disclosed in Patent Document 1, face challenges in environmental suitability and bag-making compatibility, with issues related to strength, rigidity, and transportability.

Method used

A gas barrier laminate structure comprising a paper base material, a deposited layer, a sealant film with a polyolefin resin, and optionally a barrier coat layer, where the basis weight ratio of the paper base material to the sealant film is optimized between 3.7 and 30, ensuring sufficient strength and transportability while maintaining environmental compatibility.

Benefits of technology

The proposed gas barrier laminate achieves excellent environmental suitability and sufficient bag-making compatibility, preventing breakage during transport and ensuring high gas barrier properties, while reducing plastic usage and enhancing recyclability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069801000001_ABST
    Figure 2025069801000001_ABST
Patent Text Reader

Abstract

To provide a gas barrier laminate that exhibits excellent environmental compatibility and offers sufficient suitability for bag production.SOLUTION: A gas barrier laminate according to the present disclosure has a laminated structure including a vapor-deposited layer and a sealant film in this order, wherein the sealant film contains a polyolefin resin, and assuming that the basis weight of the paper substrate is defined as X and the weight of the sealant film per m2 is defined as Y, the ratio of X to Y (X / Y) is 3.7 or more and 30.0 or less, and X is 10 g / m2 or more and 100 g / m2 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a gas barrier laminate and a packaging bag. [Background technology]

[0002] In many fields, such as food, beverages, pharmaceuticals, and chemicals, packaging materials are used according to the contents. Packaging materials are required to have gas barrier properties that prevent the permeation of water vapor and oxygen, which can cause deterioration of the contents.

[0003] In recent years, the trend toward plastic-free products has been growing due to growing environmental awareness sparked by the problem of marine plastic waste. From the viewpoint of reducing the amount of plastic materials used, the use of paper instead of plastic materials has been considered in various fields. For example, Patent Document 1 discloses a laminate that includes a paper substrate layer, a deposition layer, a sealant layer, and a barrier adhesive layer, in which the mass of the paper substrate layer and the mass of the sealant layer satisfy a specific relational formula. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2021 / 220830 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the laminate disclosed in Patent Document 1 may experience problems during transportation for bag making, and the inventors' investigations have revealed that there is room for improvement in terms of suitability for bag making.

[0006] In addition, from the viewpoint of the Law for Promoting Effective Utilization of Resources, it is required to increase the ratio of paper in the entire gas barrier laminate. The laminate disclosed in Patent Document 1 has room for improvement in terms of environmental compatibility.

[0007] The present disclosure has been made in view of the above circumstances, and provides a gas barrier laminate having excellent environmental compatibility and sufficient bag-making suitability. The present disclosure also provides a packaging bag including such a gas barrier laminate. [Means for solving the problem]

[0008] In order to solve the above problems, the present disclosure provides the following gas barrier laminate and packaging bag. [1] A paper substrate; A deposition layer; A sealant film; in this order, The sealant film contains a polyolefin resin, The basis weight of the paper base material is X, and the thickness of 1 m of the sealant film is 2 When the weight per unit is Y, the ratio of X to Y (X / Y) is 3.7 or more and 30.0 or less. X is 10g / m 2 More than 100g / m 2 A gas barrier laminate comprising: [2] The gas barrier laminate according to [1], wherein the polyolefin resin includes a polypropylene resin. [3] The gas barrier laminate according to [1] or [2], further comprising a barrier coating layer at least either between the sealant film and the deposition layer or between the deposition layer and the paper substrate. [4] The gas barrier laminate according to any one of [1] to [3], wherein the sealant film has a thickness of 4 μm or more and 15 μm or less. [5] The gas barrier laminate according to any one of [1] to [4], wherein the ratio (X / Y) is 7.0 or more and 30.0 or less. [6] The gas barrier laminate according to any one of [1] to [5], wherein the ratio (X / Y) is 16.5 or more and 30.0 or less. [7] The paper base has a basis weight of 40 g / m 2 More than 80g / m 2 The gas barrier laminate according to any one of [1] to [6] below. [8] A packaging bag comprising the gas barrier laminate according to any one of [1] to [7]. Effect of the Invention

[0009] According to the present disclosure, there is provided a gas barrier laminate having excellent environmental compatibility and sufficient bag-making suitability. Also, according to the present disclosure, there is provided a packaging bag including such a gas barrier laminate. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a gas barrier laminate according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a perspective view showing a packaging bag according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Preferred embodiments of the present disclosure will be described in detail below, however, the present disclosure is not limited to the following embodiments.

[0012] <Gas barrier laminate> FIG. 1 is a schematic cross-sectional view showing a gas barrier laminate according to one embodiment. The gas barrier laminate 10 according to one embodiment has a laminate structure including a paper substrate 1, an adhesive layer 2, a barrier coat layer 3, a deposition layer 4, and a sealant film 5, in this order. The sealant film contains a polyolefin resin. The basis weight of the paper substrate 1 is X, and the thickness of the sealant film 5 per m 2 When the weight per unit is Y, the ratio of X to Y (X / Y) is 3.7 to 30.0. The basis weight (X) of the paper base material is 15 g / m 2 More than 100g / m 2 The following is the result.

[0013] The gas barrier laminate 10 has excellent environmental suitability and sufficient suitability for bag making. The inventors speculate that the reason for this effect is as follows. That is, if the ratio (X / Y) is less than 3.7, the strength of the gas barrier laminate is insufficient and breaks when the laminate is transported for bag making. Also, if the ratio (X / Y) is more than 30.0, the rigidity of the gas barrier laminate is too high, which hinders transportation of the gas barrier laminate. The gas barrier laminate 10 has a basis weight (X) of 10 g / m 2 More than 100g / m 2 or less, and the ratio (X / Y) is 3.7 or more. This prevents the gas barrier laminate 10 from breaking during transportation, making it excellent in environmental suitability. Furthermore, the gas barrier laminate 10 has a ratio (X / Y) of 30.0 or less. This allows the gas barrier laminate 10 to have sufficient transportability. As a result, the gas barrier laminate 10 has excellent environmental suitability and sufficient bag-making suitability.

[0014] The gas barrier laminate 10 also includes a deposition layer 4 on the surface of the sealant film 5. This tends to suppress the occurrence of defects in the deposition layer 4 resulting from the unevenness of the paper base material 1, compared to when the deposition layer 4 is provided on the paper base material 1. As a result, the gas barrier laminate 10 tends to have excellent gas barrier properties. Furthermore, the gas barrier laminate 10 does not need to include a barrier coat layer for providing the deposition layer 4 on the paper base material 1. The gas barrier laminate 10 also includes a sealant film. This tends to improve bending resistance, compared to when the sealant layer is a film formed by wet coating.

[0015] The ratio (X / Y) is preferably 7.0 or more, and more preferably 16.5 or more, which makes the gas barrier laminate 10 more environmentally friendly and also makes it possible to further increase the bag making speed and the dry lamination processing speed, which tends to improve productivity.

[0016] Each layer of the gas barrier laminate 10 will now be described in detail.

[0017] [Paper base material] The paper substrate 1 is not particularly limited, and may be appropriately selected depending on the application of the packaging bag to which the gas barrier laminate 10 is applied. There is no particular limitation as long as the paper is mainly composed of plant-derived pulp. Specific examples of the paper substrate 1 include fine paper, special fine paper, coated paper, art paper, cast-coated paper, imitation paper, kraft paper, and glassine paper. The thickness of the paper substrate 1 may be, for example, 30 μm or more and 100 μm or less, or 30 μm or more and 70 μm or less.

[0018] The basis weight (X) of the paper base material is set to 30 g / m because it is more environmentally friendly and tends to improve bag making and lamination speeds. 2 It is preferable that the thickness is 40 g / m or more. 2 The basis weight (X) of the paper base material is preferably 80 g / m or more because this tends to improve the heat sealability during bag making and increase the bag making speed. 2 It is preferable that the thickness is less than 70 g / m 2 It is more preferable that:

[0019] The paper base material 1 may have a coating layer at least on the side that contacts the adhesive layer 2. The coating layer can prevent the adhesive layer 2 from soaking into the paper, and can also fill in the unevenness of the paper. The coating layer may contain, for example, various copolymers such as styrene-butadiene, styrene-acrylic, and ethylene-vinyl acetate, polyvinyl alcohol resin, cellulose resin, paraffin (wax), etc. as binder resin, and may contain clay, kaolin, calcium carbonate, talc, mica, etc. as filler.

[0020] The thickness of the coating layer may be, for example, 1 to 10 μm, or 3 to 8 μm.

[0021] The mass ratio of the paper base material 1 may be 75 mass% or more, preferably 80 mass% or more, more preferably 85 mass% or more, and even more preferably 90 mass% or more, based on the entire gas barrier laminate. When the mass ratio of the paper base material is within this range, the amount of plastic material used can be sufficiently reduced, the gas barrier laminate as a whole can be said to be made of paper, and it has excellent recyclability.

[0022] [Adhesive layer] The adhesive layer 2 adheres the paper base material 1 to the barrier coat layer 3. As the adhesive layer 2, various materials can be used as long as they adhere the paper base material 1 to the barrier coat layer 3, and examples of the adhesive layer 2 include a cured product of a urethane adhesive and a cured product of an epoxy adhesive.

[0023] <Urethane adhesive> The urethane adhesive is a resin composition containing a polyol having two or more hydroxyl groups in one molecule and an isocyanate compound having two or more isocyanate groups in one molecule. The urethane adhesive is cured to generate a urethane bond. The urethane adhesive is preferably a two-component curing type.

[0024] The urethane adhesive may have gas barrier properties. For example, the method of imparting gas barrier properties to the urethane adhesive may include a method of using a polyol having a skeleton with gas barrier properties, a method of making the resin composition contain a phosphoric acid-modified compound, and a method of making the resin composition contain a plate-shaped inorganic compound. These methods may be used alone or in combination of two or more methods.

[0025] The polyol having a skeleton with barrier properties is preferably one having a main skeleton of polyester or polyester polyurethane, the polyester containing a structure derived from an ortho-oriented aromatic dicarboxylic acid or an anhydride thereof. The polyester portion of the main skeleton may be obtained by polycondensation reaction of a polycarboxylic acid and a polyhydric alcohol.

[0026] Examples of the polycarboxylic acid include aliphatic polycarboxylic acids and aromatic polycarboxylic acids. Examples of the aliphatic polycarboxylic acid include succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid.

[0027] Examples of aromatic polybasic carboxylic acids include orthophthalic acid, terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,2-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid and anhydrides of these dicarboxylic acids, as well as polybasic acids such as p-hydroxybenzoic acid and p-(2-hydroxyethoxy)benzoic acid. The polybasic carboxylic acids can be used alone or in combination of two or more.

[0028] The polycarboxylic acid is preferably an ortho-oriented aromatic dicarboxylic acid or an anhydride thereof. The content of the ortho-oriented aromatic dicarboxylic acid or anhydride thereof is preferably 70 to 100 mass% based on the total amount of the polycarboxylic acid components constituting the polyester.

[0029] Examples of the ortho-oriented aromatic dicarboxylic acid include orthophthalic acid, 1,2-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, and anhydrides of these dicarboxylic acids.

[0030] The polyhydric alcohol includes an aliphatic polyhydric alcohol and an aromatic polyhydric phenol. The aliphatic polyhydric alcohol includes, for example, ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, cyclohexanedimethanol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, dimethylbutanediol, butylethylpropanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, and tripropylene glycol.

[0031] Examples of aromatic polyhydric phenols include hydroquinone, resorcinol, catechol, naphthalenediol, biphenol, bisphenol A, hisphenol F, and tetramethylbiphenol, as well as ethylene oxide-extended products and hydrogenated alicyclic derivatives thereof.

[0032] The isocyanate compound may be an aromatic compound having an aromatic ring, an aliphatic compound having no aromatic ring, a low molecular weight compound or a high molecular weight compound, a diisocyanate compound having two isocyanate groups or a polyisocyanate compound having three or more isocyanate groups, or a blocked isocyanate compound obtained by addition reaction with an isocyanate blocking agent.

[0033] The isocyanate compound is preferably a polyisocyanate compound from the viewpoint of the adhesiveness of the adhesive layer 2. The isocyanate compound is preferably one having an aromatic ring, since it imparts oxygen barrier properties to the adhesive layer 2, and is particularly preferably an isocyanate compound containing a meta-xylene skeleton.

[0034] Examples of the isocyanate compound include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, metaxylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and trimers of these isocyanate compounds. These isocyanate compounds may be adducts, biurets, or allophanates obtained by reacting a low molecular weight active hydrogen compound such as ethylene glycol, propylene glycol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, or metaxylylenediamine, or an alkylene oxide adduct thereof, or a high molecular weight active hydrogen compound such as various polyester resins, polyether polyols, or polyamides, with an isocyanate compound.

[0035] <Epoxy adhesive> The epoxy adhesive is a resin composition containing an epoxy resin and an epoxy resin curing agent.

[0036] The epoxy resin may have a saturated bond or an unsaturated bond, and may be any of an aliphatic compound, an alicyclic compound, an aromatic compound, and a heterocyclic compound. In order to exhibit higher gas barrier properties, the epoxy resin is preferably an epoxy resin containing an aromatic ring or an alicyclic structure in the molecule.

[0037] Examples of the epoxy resin include an epoxy resin having a glycidylamino group derived from meta-xylylenediamine, an epoxy resin having a glycidylamino group derived from 1,3-bis(aminomethyl)cyclohexane, an epoxy resin having a glycidylamino group derived from diaminodiphenylmethane, an epoxy resin having a glycidylamino group and / or a glycidyloxy group derived from para-aminophenol, an epoxy resin having a glycidyloxy group derived from bisphenol A, an epoxy resin having a glycidyloxy group derived from bisphenol F, an epoxy resin having a glycidyloxy group derived from phenol novolac, and an epoxy resin having a glycidyloxy group derived from resorcinol. The epoxy resin may be used alone or in combination of two or more kinds. From the viewpoint of gas barrier properties, the epoxy resin is preferably an epoxy resin having a glycidylamino group derived from meta-xylylenediamine and an epoxy resin having a glycidyloxy group derived from bisphenol F, and more preferably an epoxy resin having a glycidylamino group derived from meta-xylylenediamine.

[0038] The epoxy resin hardener may be a reaction product of meta- or para-xylylenediamine with an unsaturated carboxylic acid and / or a derivative thereof, as shown in formula (1) below.

[0039] [ka] [In formula (1), R 1 represents an alkyl group having 1 to 8 carbon atoms, an aralkyl group having 1 to 8 carbon atoms, or an aryl group.]

[0040] By using metaxylylenediamine or paraxylylenediamine as a precursor of an epoxy resin curing agent, the gas barrier property is further improved. From the viewpoint of gas barrier property, metaxylylenediamine is preferable. Metaxylylenediamine or paraxylylenediamine may be used alone or in combination of two or more.

[0041] By using the unsaturated carboxylic acid and / or its derivative represented by the above formula (1) as a precursor of the epoxy resin curing agent, good adhesiveness is exhibited. The unsaturated carboxylic acid and / or its derivative represented by the above formula (1) include unsaturated carboxylic acids such as crotonic acid, 2-pentenoic acid, 2-hexenoic acid, 4-methyl-2-pentenoic acid, 2-heptenoic acid, 4-methyl-2-hexenoic acid, 5-methyl-2-hexenoic acid, 4,4-dimethyl-2-pentenoic acid, 4-phenyl-2-butenoic acid, cinnamic acid, o-methylcinnamic acid, m-methylcinnamic acid, p-methylcinnamic acid, 2-octenoic acid, 2-nonenoic acid, 2-decenoic acid, and 2-undecenoic acid, and derivatives thereof (e.g., esters, amides, acid anhydrides, acid chlorides, etc.), but are not particularly limited thereto. The unsaturated carboxylic acid and / or its derivative represented by the above formula (1) may be used alone or in combination of two or more.

[0042] The unsaturated carboxylic acid and / or its derivative represented by the above formula (1) is preferably a carboxylic acid having a structure in which R 1 is preferably at least one selected from the group consisting of unsaturated carboxylic acids and derivatives thereof, in which R is a hydrocarbon group or a phenyl group having 1 to 3 carbon atoms, more preferably at least one selected from the group consisting of crotonic acid and crotonic acid derivatives, and even more preferably at least one selected from the group consisting of crotonic acid and crotonic acid esters. As the crotonic acid ester, an alkyl ester having 1 to 3 carbon atoms is more preferable, and methyl crotonate is even more preferable.

[0043] The adhesive layer 2 may be formed using a one-component curing or two-component curing adhesive (dry lamination method), may be formed using a solvent-free adhesive (non-solvent dry lamination method), or may be formed by extruding molten resin onto the surface of the paper substrate 1 or the barrier coating layer 3 (extrusion lamination method).

[0044] From the viewpoint of improving the adhesiveness of the adhesive layer 2, the thickness of the adhesive layer 2 is preferably 0.01 μm or more, and more preferably 3 μm or more, and is preferably 10 μm or less since the amount of plastic material used can be further reduced.

[0045] [Barrier coat layer] The barrier coat layer 3 is provided on the surface of the vapor deposition layer 4 to improve adhesion between the paper base material 1 and the vapor deposition layer 4 and to improve the gas barrier properties of the gas barrier laminate. The barrier coat layer 3 is not particularly limited, but preferably contains a polyvinyl alcohol-based resin and a polyolefin having a polar group, as this provides better gas barrier properties (particularly water vapor barrier properties), and more preferably contains a polyvinyl alcohol-based resin, as this provides better water vapor barrier properties and oxygen barrier properties.

[0046] By including a polyolefin having a polar group in the barrier coat layer 3, a dense film can be formed due to the crystallinity of the polyolefin, and water vapor barrier properties are exhibited. The crystallinity of the polyolefin exhibits water vapor barrier properties, and the presence of a polar group exhibits adhesion to the deposition layer 4.

[0047] The polyolefin having a polar group may have at least one selected from a carboxyl group, a salt of a carboxyl group, a carboxylic anhydride group, and a carboxylic ester.

[0048] As the polyolefin having a polar group, a copolymer of ethylene or propylene with an unsaturated carboxylic acid (an unsaturated compound having a carboxyl group, such as acrylic acid, methacrylic acid, or maleic anhydride), an unsaturated carboxylic acid ester, or a salt obtained by neutralizing a carboxylic acid with a basic compound may be used. In addition, a copolymer of vinyl acetate, an epoxy compound, a chlorine compound, a urethane compound, a polyamide compound, or the like may also be used.

[0049] Specific examples of polyolefins having a polar group include copolymers of acrylic acid ester and maleic anhydride, ethylene-vinyl acetate copolymers, and ethylene-glycidyl methacrylate copolymers.

[0050] The polyvinyl alcohol resin is, for example, a fully saponified polyvinyl alcohol resin, a partially saponified polyvinyl alcohol resin, a modified polyvinyl alcohol resin, an ethylene-vinyl alcohol copolymer resin, etc. The degree of polymerization of the polyvinyl alcohol resin is preferably 300 or more and 1700 or less. If the degree of polymerization is 300 or more, the gas barrier properties and bending resistance of the gas barrier laminate become good, and if the degree of polymerization is 1700 or less, the viscosity of the coating liquid of the polyvinyl alcohol resin described below becomes low, and the coating property becomes good.

[0051] When the barrier coat layer 3 contains a polyvinyl alcohol-based resin, it has excellent flexibility, and can suppress cracking of the deposition layer described below after bending (folding), thereby suppressing deterioration of the gas barrier properties, and can improve adhesion between the deposition layer and the barrier coat layer 3.

[0052] The barrier coat layer 3 may contain other components in addition to the above-mentioned polyolefin and polyvinyl alcohol resins. Examples of the other components include resins such as polyolefins other than the above-mentioned polyolefins, polyacrylics, polyesters, polyurethanes, polyethyleneimines, polylactic acids, polyamides, starch and its derivatives, and cellulose derivatives, as well as additives such as silane coupling agents, organic titanates, glycerin, glycols, casein, and wax.

[0053] The total content of the polyolefin and polyvinyl alcohol resin in the barrier coat layer 3 may be, for example, 50% by mass or more, 70% by mass or more, 90% by mass or more, or 100% by mass.

[0054] The thickness of the barrier coat layer 3 may be, for example, 0.1 μm or more, 1 μm or more, 20 μm or less, 10 μm or less, or 5 μm or less. If the thickness of the barrier coat layer 3 is 0.1 μm or more, more stable barrier properties can be ensured. Also, if the thickness of the barrier coat layer 3 is 20 μm or less, the gas barrier laminate 10 has better environmental suitability.

[0055] Examples of the solvent contained in the coating liquid for the barrier coat layer 3 include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. These solvents may be used alone or in combination of two or more. Among these, from the viewpoint of characteristics, methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred. Furthermore, from the viewpoint of the environment, methyl alcohol, ethyl alcohol, isopropyl alcohol, and water are preferred.

[0056] The method of providing the barrier coat layer 3 is not particularly limited. When the barrier coat layer 3 contains at least one of the above-mentioned polyolefin and polyvinyl alcohol-based resin, it can be obtained by applying a coating liquid containing at least one of the above-mentioned polyolefin and polyvinyl alcohol-based resin and a solvent onto the deposition layer and drying it. In addition, polyolefin wax may be added from the viewpoint of preventing blocking. The polyolefin wax in the coating liquid should have a large particle size so that the contact area is small. Although not particularly limited, the particle size may be specifically 0.1 μm or more, 1 μm or more, 10 μm or less, 7 μm or less, or 5 μm or less.

[0057] [Vapour-deposited layer] The vapor-deposited layer 4 is a layer formed by vapor-depositing a metal or an inorganic compound. The vapor-deposited layer 4 is provided on the surface of the sealant film 5 so as to be in contact with the sealant film 5.

[0058] The deposition layer 4 may be one obtained by depositing aluminum, such as aluminum oxide (AlO x ), silicon oxide (SiO x ) etc.

[0059] The thickness of the deposited layer 4 may be appropriately set depending on the application, but may be preferably 10 nm or more, 30 nm or more, 50 nm or more, and may be 300 nm or less, 100 nm or less, 80 nm or less. By setting the thickness of the deposited layer 4 to 10 nm or more, it is easy to ensure sufficient continuity of the deposited layer 4, and by setting the thickness to 300 nm or less, it is easy to sufficiently suppress the occurrence of curling and cracking, and to easily achieve sufficient gas barrier performance and flexibility.

[0060] From the viewpoint of oxygen gas barrier performance and film uniformity, it is preferable to form the deposition layer 4 by a vacuum deposition method. There are known deposition methods such as vacuum deposition, sputtering, and chemical vapor deposition (CVD), but vacuum deposition is preferred because of its fast deposition rate and high productivity. Among the vacuum deposition methods, deposition by electron beam heating is particularly effective because the deposition rate can be easily controlled by the irradiation area and electron beam current, and the temperature of the deposition material can be raised and lowered in a short time.

[0061] [Sealant film] The sealant film 5 contains a polyolefin resin. As the polyolefin resin, an ethylene-based resin such as low-density polyethylene resin (LDPE), medium-density polyethylene resin (MDPE), high-density polyethylene resin (HDPE), linear low-density polyethylene resin (LLDPE), ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, or ethylene-(meth)acrylic acid copolymer, a polypropylene-based resin such as homopolypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, or propylene-α-olefin copolymer, or a mixture thereof, or the like can be used. As the polyolefin resin, a polypropylene resin is preferable. Since the polypropylene resin has high rigidity, the gas barrier laminate 10 tends to have better suitability for bag making.

[0062] The content of the polyolefin resin may be 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, or may be 100% by mass, based on the total amount of the sealant film. The content of the polyethylene resin may be 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, or may be 100% by mass, based on the total amount of the sealant film. The content of the polypropylene resin may be 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, or may be 100% by mass, based on the total amount of the sealant film.

[0063] Examples of resins other than polyolefin resins include polyester resins, polylactic acid, and polybutylene succinate.

[0064] 1m of sealant film 2 The weight per unit (Y) is 3.0g / m 2 or more, and 2 It may be the following:

[0065] The sealant film may be unoriented, uniaxially oriented, or biaxially oriented.

[0066] A biaxially oriented polypropylene resin film can be suitably used as the sealant film. A biaxially oriented polypropylene resin film requires heat sealing at high temperatures. In particular, when paper is used as the substrate, the thickness of the paper may prevent heat from being transferred to the film during bag making, resulting in insufficient sealing. However, the gas barrier laminate 10 has a ratio (X / Y) of 3.7 or more and 30.0 or less. This means that the gas barrier laminate 10 tends to maintain transportability and have sufficient heat sealability even when a biaxially oriented polypropylene resin film is used.

[0067] The thickness of the sealant layer is preferably 4 μm or more from the viewpoint of durability against heat when forming the vapor deposition layer, and is preferably 15 μm or less in order to further reduce the amount of plastic material used.

[0068] Although the embodiments of the present disclosure have been described in detail above, the present invention is not limited to the above-mentioned embodiments. For example, the gas barrier laminate according to the other embodiments may not have a barrier coat layer. Also, the gas barrier laminate according to the other embodiments may have a barrier coat layer located between the deposition layer and the sealant film, not between the adhesive layer and the deposition layer. Also, the gas barrier laminate according to the other embodiments may have a barrier coat layer located between the deposition layer and the sealant film, in addition to the barrier coat layer located between the adhesive layer and the deposition layer.

[0069] <Packaging bag> 2 is a perspective view showing a gusset bag 20 made of a gas barrier laminate 10. A packaging bag is produced by sealing the opening at the top of the gusset bag 20. The gusset bag 20 has portions where the gas barrier laminate 10 is folded (folded portions B1, B2). The folded portion B1 is a portion where the gas barrier laminate 10 is folded in a valley direction when viewed from the innermost layer side, while the folded portion B2 is a portion where the gas barrier laminate 10 is folded in a mountain direction when viewed from the innermost layer side.

[0070] The packaging bag may be formed into a bag shape by folding one gas barrier laminate in half so that the sealant films 5 face each other, then folding appropriately into the desired shape and heat sealing, or may be formed into a bag shape by stacking two gas barrier laminates together so that the sealant films 5 face each other, and then heat sealing.

[0071] In the packaging bag according to the present embodiment, the heat seal strength may be 2 N or more, or may be 10 N or more. The upper limit of the heat seal strength is not particularly limited, but may be, for example, 20 N or less.

[0072] The packaging bag can contain food, medicine, and the like. It is particularly suitable for containing food, such as sweets. The packaging bag according to the present embodiment can maintain high gas barrier properties even in a shape having a folded portion.

[0073] In this embodiment, a gusset bag is given as an example of a packaging bag, but the gas barrier laminate according to this embodiment may be used to produce, for example, a pillow bag, a three-side sealed bag, or a standing pouch. EXAMPLES

[0074] Hereinafter, the present disclosure will be described more specifically based on examples and comparative examples, but the present disclosure is not limited to the following examples.

[0075] [Manufacturing of gas barrier laminate] (Examples 1 to 30 and Comparative Examples 1 to 3) A sealant film with the material, thickness, density, and weight shown in Table 1 was prepared as the sealant film for each Example and Comparative Example. Aluminum was vapor-deposited on one surface of the sealant film. This resulted in a first laminate with an aluminum vapor-deposited layer (thickness: 140 nm) formed on the sealant film. A paper base material with the basis weight shown in Table 1 was prepared as the paper base material for each Example and Comparative Example. The first laminate and the paper base material were bonded together with an adhesive (manufactured by Mitsui Chemicals, Inc., product name: base agent Takelac PP6263 / hardener Takenate A50, application amount: 3 g / m) so that the vapor-deposited layer of the first laminate faced the paper base material. 2 ) was used. This resulted in a gas barrier laminate. In Table 1, Torayfan manufactured by Toray Industries, Inc. was used as the sealant film with a thickness of 12 μm and made of OPP (biaxially oriented polypropylene resin). In Table 1, a product manufactured by Ube Film Co., Ltd. was used with a thickness of 9 μm and made of HDPE (high density polyethylene resin).

[0076] (Examples 31 to 33) A first laminate was obtained in the same manner as in Example 1, except that a sealant film with the material, thickness, density, and weight shown in Table 1 was used. A coating solution containing polyvinyl alcohol (manufactured by Kuraray Co., Ltd., product name: "Poval", coating amount: 4 g / m) was applied to the surface of the first laminate on the deposition layer side. 2 ) was applied to obtain a coating film. The coating film was dried to form a barrier coat layer. This resulted in a second laminate having a sealant film, a vapor deposition layer, and a barrier coat layer in this order. Paper substrates of the basis weights shown in Table 1 were prepared as paper substrates for each Example. The second laminate and the paper substrate were bonded together using a two-component adhesive (manufactured by Mitsui Chemicals, Inc., product name: base agent Takelac PP6263 / hardener Takenate A50, application amount: 3 g / m) so that the barrier coat layer of the second laminate and the paper substrate faced each other. 2 ) to obtain a gas barrier laminate.

[0077] Comparative Example 4 A sealant film having the material, thickness, density, and weight shown in Table 1 was prepared. A paper substrate having the basis weight shown in Table 1 was prepared. The sealant film and the paper substrate were bonded together using a two-component adhesive (manufactured by Mitsui Chemicals, Inc., product name: base agent Takelac PP6263 / hardener Takenate A50, application amount: 3 g / m 2 ) to obtain a gas barrier laminate.

[0078] Comparative Example 5 A paper substrate with the basis weight shown in Table 1 was prepared as the paper substrate. Aluminum was vapor-deposited on one surface of the paper substrate. This resulted in a first laminate with an aluminum vapor-deposited layer (thickness: 140 nm) formed on the paper substrate. A sealant film with the material, thickness, density, and weight shown in Table 1 was prepared as the sealant film. The first laminate and the sealant film were bonded together using a two-component adhesive (manufactured by Mitsui Chemicals, Inc., product name: base agent Takelac PP6263 / hardener Takenate A50, application amount: 3 g / m) so that the vapor-deposited layer of the first laminate and the sealant film faced each other. 2 ) to obtain a gas barrier laminate.

[0079] [Environmental suitability] For the gas barrier laminate obtained in each example, the mass ratio of the paper base material based on the entire gas barrier laminate was measured. The measurement results were evaluated according to the following criteria. The results are shown in Table 2.

[0080] (standard) A: The mass ratio of the paper base material is 85% or more by mass. B: The mass ratio of the paper base material is 75% by mass or more and less than 85% by mass. C: The mass ratio of the paper base material is less than 75 mass%

[0081] [Bag making suitability] The gas barrier laminates obtained in each example were used to make three-sided pouches (height: 10 cm, width: 7.7 cm) using a bag making machine manufactured by Taisei Lamic Co., Ltd. The bag making speed was 45 bags / min. The results are shown in Table 2, with "A" indicating cases where packaging bags could be made and "B" indicating cases where they could not be made. In addition, for the gas barrier laminates from which packaging bags could be made, the maximum bag making speed at which the gas barrier laminate could be made without breakage or problems with transporting was measured. The maximum value was evaluated according to the following criteria.

[0082] (standard) A: Maximum bag making speed is 90 bags / min or more B: The maximum bag making speed is between 50 and 90 pcs / min. C: The maximum bag making speed is less than 50 bags / min.

[0083] [Processing suitability] The gas barrier laminate obtained in each example was dry laminated to measure the maximum delivery speed at which wrinkles did not occur. A dry laminating machine was used for dry lamination. Specifically, the original roll of the sealant film was attached to the first paper feed section of the dry laminating machine, and the original roll of the paper substrate was attached to the second paper feed section. The sealant film was delivered from the first paper feed section, and an adhesive was applied to the sealant film by the direct gravure method to form a coating film. The sealant film on which the coating film was formed was passed through an oven to dry the coating film. Thereafter, the sealant film and the paper substrate delivered from the second paper feed section were bonded together via the dried product of the adhesive coating film. A heat roll was used for bonding, and the heat roll was set to 60°C.

[0084] (standard) A: The maximum delivery speed is 200m / min or more. B: The maximum feed speed is 100 m / min or more and less than 200 m / min. C: The maximum feed speed is 50 m / min or more and less than 100 m / min. D: The maximum delivery speed is less than 50 m / min.

[0085] [Gas barrier properties] The oxygen transmission rate (OTR) of the gas barrier laminate obtained in each example was measured in accordance with JIS K-7126-2 at a temperature of 30°C and a relative humidity of 70% using an oxygen transmission rate measuring device (manufactured by MOCON, product name: OX-TRAN 2 / 22). The measurement results were evaluated according to the following criteria, with "B" or higher being considered good. The results are shown in Table 2.

[0086] (standard) A: 25cc / (m 2 ·day·atm) B: 25cc / (m 2 ·day · atm) or more 50cc / (m) 2 ·day·atm) C: 50cc / (m 2 ·day · atm) or more

[0087] [Table 1]

[0088] [Table 2] [Explanation of symbols]

[0089] Reference Signs List 1: paper substrate, 3: barrier coating layer, 4: deposition layer, 5: sealant film, 10: gas barrier laminate.

Claims

1. A paper substrate; A deposition layer; A sealant film; in this order, The sealant film contains a polyolefin resin, The basis weight of the paper base material is X, and the sealant film has a thickness of 1 m 2 When the weight per unit area is Y, the ratio of X to Y (X / Y) is 3.7 or more and 30.0 or less, The X is 10 g / m 2 More than 100g / m 2 A gas barrier laminate comprising:

2. The gas barrier laminate according to claim 1 , wherein the polyolefin resin comprises a polypropylene resin.

3. The gas barrier laminate according to claim 1 , further comprising a barrier coat layer at least one between the sealant film and the deposition layer and between the deposition layer and the paper substrate.

4. 2. The gas barrier laminate according to claim 1, wherein the sealant film has a thickness of 4 μm or more and 15 μm or less.

5. The gas barrier laminate according to claim 1 , wherein the ratio (X / Y) is 7.0 or more and 30.0 or less.

6. The gas barrier laminate according to claim 1 , wherein the ratio (X / Y) is 16.5 or more and 30.0 or less.

7. The paper base material has a basis weight of 40 g / m 2 80g / m or more 2 The gas barrier laminate according to claim 1 , wherein:

8. A packaging bag comprising the gas barrier laminate according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Laminate and package using same

    WO2021220830A1

Cited By

  • Packaging material, packaging bag, gas barrier laminate, and method for manufacturing gas barrier laminate

    WO2025243797A1